Clustering Junior Schools in Implementing Smart School Using The K-Means in Pekanbaru - Nisa, Aida; Anam, M. Khairul; Yenni, Helda; Kudadiri, Parlindungan; Gunadi (Jurnal Sains, Nalar, dan Aplikasi Teknologi Informasi, 2024)
The purpose of this research is to determine the readiness of schools in implementing the Smart School system through various stages. One of the concepts of a Smart City involves integrating information and communication technology into the learning process at every school to create Smart Schools. However, not all schools are ready to implement this technology because it requires suitable technology to support the quality of teaching and learning. Another issue is the absence of information systems that can facilitate administrative tasks and the teaching and learning process. The use of the K-Means method is beneficial for clustering schools based on their stages, characteristics, and readiness to implement the Smart School system. This helps identify schools with the highest level of readiness. This research demonstrates that the use of K-Means can identify school readiness based on the established stages related to the Smart School system. It also can pique students' interest in developing and boosting the school's reputation as the best technology-based school.